2003
DOI: 10.1046/j.1365-2559.2003.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibromyxoid tumour of soft parts, with focus on unusual clinicopathological features

Abstract: Though a distinct entity, ossifying fibromyxoid tumour may exhibit a wider clinicopathological spectrum than generally recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In this case, the finding of an encapsulated lobulated tumor of eosinophilic spindly cells with vesicular nuclei is as described by previously reported cases [1,[4][5][6] . Although the fibromyxoid component of OFMT might suggest a fibroblastic origin, the expression of both S100 and NSE proteins by the tumor cells point instead to a neural origin [1] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this case, the finding of an encapsulated lobulated tumor of eosinophilic spindly cells with vesicular nuclei is as described by previously reported cases [1,[4][5][6] . Although the fibromyxoid component of OFMT might suggest a fibroblastic origin, the expression of both S100 and NSE proteins by the tumor cells point instead to a neural origin [1] .…”
Section: Discussionsupporting
confidence: 80%
“…Although the fibromyxoid component of OFMT might suggest a fibroblastic origin, the expression of both S100 and NSE proteins by the tumor cells point instead to a neural origin [1] . Further support for a neural histogenesis is provided by the discovery of Holck et al [6] of an interrupted basal lamina, a Schwannian feature in some of the reported cases [1,3,7] , and the demonstration of cytogenetic abnormalities involving chromosomes 6 and 18 also resonated with a malignant peripheral nerve sheath tumor.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to a few large series [1,[4][5][6][7], there are many case reports describing a single or a few cases [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although the extremities, trunk, and head and neck are prevailing sites, unusual locations, such as the retroperitoneum and mediastinum, were also recognized [11,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Both tumors possess abundant fibromyxoid stroma and may show S-100 protein immunoreactivity. For the distinction, ultrastructural investigation seems to be useful, in that extraskeletal myxoid chondrosarcoma usually contains unique intraendoplasmic microtubules and lacks welldeveloped, reduplicated basal laminae [33], which seem, to the contrary, to be an invariable, unique feature of OFMT [1,5,6,10,14,18,20]. In spite of the diverse immunophenotype, ultrastructural features are quite homogeneous.…”
mentioning
confidence: 99%
“…[23][24][25] This subcutaneous tumor usually occurs on the proximal extremities (or head and neck) of adult males, with a mean age of 47 years. On histologic examination, this lesion is situated in the subcutaneous tissue and has a fibrous capsule encircling lobules and fascicles of round to fusiform cells in a focally myxoid matrix.…”
Section: Discussionmentioning
confidence: 99%